Pengaruh Umur Panen Dan Dosis Pupuk Organik Cair Limbah Pasar Tradisional Pada Tinggi Tanaman Dan Produksi Segar Rumput Setaria - Perdana, Yoga Bekti; Hendarto, Eko; Hidayat, Nur (ANGON: Journal of Animal Science and Technology, 2019)
Background. The purpose of this research was to know the effect of defoliation periode and liquid fertlizer made of traditional market organic wastes dosage on the heights plant and fresh weight of setaria grass (setaria splendida stapf). Materials and methods. The material used is setaria grass as many as 756 cuttings, 3,25 liter traditional market waste liquid organic fertilizer, and 5,75liter water. The research method is experimental and the design used is Completely Randomized Design (CRD) the pattern faktorial with 12 treatments and 3 replications. Results. The results of research showed that effect defoliation periode for highest average height plant of setaria grass on the treatment W49 that is 49,61 cm. The results of research showed that effect defoliation periode for lowest average height plant of setaria grass on the treatment W35 that is 36,79 cm. The results of research showed that effect defoliation periode for highest average fresh weight of setaria grass on the treatment W49 that is 0,81 kg/m2. The results of research showed that effect defoliation periode for lowest average fresh weight of setaria grass on the treatment W35 that is 0,50 kg/m2. The results of analysis of variance showed that the use of liquid fertlizer made of traditional market organic wastes had no significant effect (P > 0,05) on the hights plant and fresh weight of setaria grass, but defoliation periode had very significant effect (P < 0,01). Conclusion. Based on these results, traditional market waste liquid organic fertilizer using the good dosage or be able combination with fertilizers other that incrase toproduction setaria grass.